The effects of childhood adversity: two specific neural patterns - Yan, Linlin; Kraaijenvanger, Eline J.; Wennekers, Ricardo; Müller, Veronika I.; Eickhoff, Simon B.; Fernández, Guillén; Holz, Nathalie E.; Kohn, Nils (Neuroscience & biobehavioral reviews, 2025)
Childhood adversity (CA) is associated with an elevated risk of psychopathology across the lifespan and altered brain functions are thought to play an important role in linking CA to mental vulnerability. Previous research has proposed that CA generally influences emotion processing and particularly affects reward processing and cognitive control, yet convergent evidence for CA-related neural and functional networks underlying these processes remains to be fully understood. To investigate the impact of CA on functional brain activations, the present study performed Activation Likelihood Estimation (ALE) analyses across neuroimaging studies involving three task domains: emotion processing, cognitive control, and reward processing. ALE results revealed two significant CA-related convergences of activation in the left amygdala and insula. To better understand and characterize the functions of these ALE-derived clusters, we applied the Meta-Analytic Connectivity Modeling (MACM) approach to identify co-activation maps, and the functional decoding approach to reveal cluster-related psychological processes. Results demonstrated two distinct neural and functional networks in CA: an amygdala-centered emotion processing network and an insula-centered somatomotor processing network. These specific neural patterns indicate the effect of CA on multiple neural and functional networks engaged in sensory-motor and emotion processing functions. Our results provide insights into the neurobiological embedding associated with CA.